ONE ROOF SYSTEM LEMBAGA PERADILAN AGAMA DI BAWAH KEKUASAAN MAHKAMAH AGUNG - Zuhriah, Erfaniah (Fakultas Syariah, 2009)
History of judiciary power in Indonesia judicial institutions is quite long and dilemmatic. The political situation in Indonesia has a major impact on the existence of judicial institutions. Independence of judiciary power is not met a demand for years. It is proved by the interventions of extra-judicial government institutionsÂ to judicial institutions. The Supreme Court, as Indonesia's top court, at first has supervised General Courts, Religious Courts, State l Administration Court and the Military Courts only in judicial technical. Meanwhile, for non-judicial technical matters, those judicial institutions have been supervised by each government departments respectively. But with the enactment of Act No. 35 Year 1999 on Amendment of Act No. 14 Year 1970, which was enhanced by Act No. 4 Year 2004 on Judiciary Power, cultivation of non-judicial technical in those judicial institutions, including Religious Court have been held by the Supreme Court.Sejarah kekuasaan kehakiman lembaga-lembaga peradilan di Indonesia cukup panjang danÂ dilematik. Situasi politik yang bergolak di Indonesia, berpengaruh besar terhadap eksistensi lembaga-lembaga peradilan. Independensi kekuasaan kehakiman tidak terpenuhi selama bertahun-tahun. Terbukti dengan banyaknya intervensi lembaga pemerintah ekstra-yudisial terhadap lembaga peradilan.Mahkamah Agung, sebagai puncak peradilan di Indonesia, pada mulanyaÂ hanya membina Peradilan Umum, Peradilan Agama, Peradilan Tata Usaha Negara dan Peradilan Militer secara teknis yudisial saja. Untuk urusan teknis non-yudisial,pembinaan lembaga-lembaga peradilan tersebut dibawah naungan departemen pemerintahan masing-masing. Namun seiring diundangkannya Undang-Undang Nomor 35 Tahun 1999 tentang Perubahan Atas Undang-Undang Nomor 14 Tahun 1970, yang kemudian disempurnakan dengan Undang-Undang Nomor 4 Tahun 2004 tentang Kekuasaan Kehakiman, pembinaan teknis non-yudisial lembaga-lembaga peradilan, termasuk Pengadilan Agama dipegang oleh Mahkamah Agung.Keywords: Sistem Satu Atap, Mahkamah Agung, Pengadilan Agama.